Spotify Application Training in Making Radio Dramas as Extracurricular Activities for Literary Studios at Schools - Een Nurhasanah; Sumiyadi Sumiyadi; Nina Puspitaloka (International Journal Of Community Service, 2023)
The extracurricular presence of literature has a role as part of literature learning in schools. Its existence provides extra space for students to deepen their insights into theory, appreciation and production of literary works as they can in the classroom. The purpose of this community service activity that is integrated with the Real Work Lecture is to provide solutions offered to overcome a problem. The solution carried out is by Training the Spotify Application in Making Radio Dramas as Extracurricular Activities for Literary Studios in Schools. The results of the activities of this community service activity program are: 1) Profiles of target groups that are able to self-help products as activities that encourage discipline, independence and knowledge; 2) Knowledge of the steps of making a radio drama which includes dubbing, script surgery, sound editing process, and uploading to the Spotify application; 3) Increase cooperation between the university and the school; 4) The creation of student discipline in spotify application training.